Babies' transition between family and early childhood education and care: a mosaic of discourses about quality of services. Issue 4 (19th October 2020) - Tebet, Gabriela Guarnieri de Campos; Lopes dos Santos, Natália; Costa, Julia; Santos, Bruna Lima; Pontes, Loani Cristina Buzo; de Oliveira, Sabrina; Ângela D'Andrea, Maria
ABSTRACT: This article aims to discuss the quality of early childhood education and care in Brazil and the process of infants' and toddlers' Inserimento to daycare. The theoretical framework of our arguments is based on the notion of quality of child education as a negotiated concept, and by the Italian concept of Inserimento . The methodology is based on the Mosaic Approach, a participative method to listen to young children. As part of the methodology, we participated in the inserimento process in five municipalities in southeastern Brazil, from 2016 and 2020. Data analysis was based on the pedagogy of listening and on studies on gender and racial relationships. The results show how laws, normative documents, family expectations, planning and routine of childhood education, available toys, space, babies, families, and professionals creates a complex mosaic of discourses about what constitutes the quality of childhood education in the babies' first days in daycare centers.